INNOVATIVE INFORMATION TECHNOLOGIES IN ELECTION POLITICAL COMMUNICATIONS - Анна РУДНЄВА (Епістемологічні дослідження у філософії, соціальних і політичних науках)
The article delves into the transformative role of digital technologies in modern electoral campaigns. The author emphasizes the role of social media in shaping public opinion. The study uses examples such as Joe Biden’s and Kamala Harris’s campaigns to illustrate how these tools can enhance visibility and engagement. The article notes that while social media significantly impacts voter awareness and fundraising, it does not guarantee electoral victories. Mobile applications are highlighted as another critical component of political strategies. The study examines India’s Namo app, which showcases how technology can foster direct communication between political leaders and citizens while collecting valuable data for campaign strategies. The author also addresses the risks associated with these technologies. The use of AI to create deepfakes and spread disinformation poses ethical and security challenges. The text concludes that while digital technologies offer immense opportunities for enhancing electoral communication, they also require robust ethical guidelines and regulatory oversight. By analyzing various tools, practices, and case studies, the article underscores the dual role of innovative information technologies in electoral communications: as catalysts for engagement and as potential vectors for manipulation. This duality necessitates a balanced approach that leverages technological benefits while safeguarding democratic principles.